Parental comprehension and satisfaction in informed consent in paediatric clinical trials: a prospective study on childhood leukaemia. Issue 10 (15th June 2010) - Chappuy, H; Baruchel, A; Leverger, G; Oudot, C; Brethon, B; Haouy, S; Auvrignon, A; Davous, D; Doz, F; Tréluyer, J M
Abstract : Objective: To evaluate the extent to which parents are satisfied with and understand the information they are given when their consent is sought for their child to participate in a phase III randomised clinical trial and the reasons for their decision. Patients and method: The authors carried out a prospective study. The authors included all parents whose consent was sought for their child to participate in the FRALLE 2000A protocol (acute lymphoblastic leukaemia) at two centres. The parents were questioned twice by a qualified psychologist using a semidirected interview, 1 and 6 months after consent was sought. Results: 43 first interviews were carried out. All the parents declared they were satisfied with the explanations provided by the physician. 35 (81%) parents felt that the information provided with the request for consent was appropriate. Eight (19%) parents did not realise that their child had been included in a research protocol. 16 (39%) parents did not understand the concept of randomisation. Half the parents could explain neither the aim of the clinical trial nor the potential benefit of inclusion to their child. Only one third of the parents were aware that they had an alternative. The principal factor underlying their decision, as stated by 29 parents (67%), was confidence in the medical team. Conclusions: The parents signed consent forms without having fully understood all the elements specific to the experimental protocol. Rather, the parents based their decision on their confidence in the medical team, even when their child's life was at risk.